One-pot synthesis of quercetin-functionalized silver and copper nanoparticles for enhanced optical, antimicrobial, and computational properties - Aziz, Dara Muhammed; Amin, Alla Ahmed Muhammed; Hassan, Sangar Ali; Ozmen, Habibe; Incili, Gokhan Kursad; Say, Yakup (Nature Portfolio, 2025)
The emergence of multidrug-resistant bacterial strains has intensified the need for novel antimicrobial agents. Herein, we report a facile one-pot green synthesis of quercetin-stabilized silver (Qn@AgNPs) and copper (Qn@CuNPs) nanoparticles using quercetin as both reductant and capping ligand. The resulting nanocomposites were fully characterized by UV-Vis spectroscopy (surface plasmon resonance peaks at 420 nm for Ag and 580 nm for Cu), FTIR (confirming quercetin-metal coordination), SEM/EDX (spherical particles, and XRD (face-centered cubic Ag and Cu phases). Density functional theory (B3LYP/3-21G) calculations yielded frontier molecular orbital gaps of 0.164 eV for Qn@AgNPs and 0.245 eV for Qn@CuNPs, with corresponding high softness values (12.20 and 8.16 eV(-)(1)), indicating enhanced electron-transfer propensity. Molecular electrostatic potential maps revealed increased charge polarization around the metal centers. Antibacterial assays against Escherichia coli and Staphylococcus aureus demonstrated minimum inhibitory concentrations of 2.11 +/- 1.22 mu g/mL and 4.69 +/- 2.68 mu g/mL for Qn@AgNPs, and 7.50 +/- 0.00 mu g/mL and 6.25 +/- 0.17 mu g/mL for Qn@CuNPs, significantly outperforming free quercetin (188 and 375 mu g/mL). In silico docking against the S. epidermidis TcaR regulator (PDB: 1KZN) and E. coli DNA gyrase B (PDB: 1HSK) revealed strong binding affinities (-7.54 to - 10.15 kcalmol(-)(1)), consistent with the observed antimicrobial potency. This integrated experimental-computational study elucidates the mechanistic underpinnings of quercetin-mediated nanoparticle bioactivity and provides a rational framework for designing next-generation flavonoid-functionalized metal nanotherapeutics.
Keywords: Nanocomposite; Simulation; Antibacterial; Green synthesis; Docking; DFT